IMPLEMENTASI KEBIJAKAN PROGRAM RUJUK BALIK PESERTA JKN PADA RUMAH SAKIT PTPN VIII SUBANG - Jajat Sudrajat (Dinamika : Jurnal Ilmiah Ilmu Administrasi Negara, 2020)
This research generally aims to determine how the Hospital Reconcile Program Policy Implementation at Hospital PTPN VIII Subang. While in particular is to determine whether the Hospital Reconcile Program Policy Implementation is successful in its implementation.In this study the author uses descriptive method, the research conducted to describe the problems that were ongoing at the time the research was conducted, whereas the approach used in this study is a qualitative approach.Thus the hypothesis of this study the Hospital Reconcile Program Policy Implementation At Hospital PTPN VIII Subang that succesfully determined by The Content Policy, Implementer (Executor)Policy and Enviorenmental Policy, and may be said that the implementation has not been successful.Based on research result relating to the above there factors, it can be obtained conclusion that basically the above three factors have not effect on the successs of the Hospital Reconcile Program Policy Implementation at Hospital PTPN VIII Subang.